Significant spatiotemporal heterogeneity in drivers of water yield Service in Agro-pastoral Ecotone of Gansu, China - Li, Jie; Li, Guang; Ma, Weiwei; Wu, Jiangqi; Lu, Yanhua; Liang, Yunliang (Frontiers in Ecology and Evolution, 2023)
Most previous studies on water yield service (WYs) analyzed the driving factors of WYs from a holistic perspective,but ignored the spatial heterogeneity and development of the driving factors. Using Invest model, Random Forest (RF)model and Geographically and Temporally Weighted (GTWR) model, we first examined the spatial distribution characteristics of WYs in agro-pastoral ecotone of Gansu China (AEGC) from 2000 to 2020. Secondly, the driving mechanism behind the spatiotemporal variation of WYs was discussed. The results show that: (1) In recent 20 years, the average annual WYs of AEGC was 110.52 mm, and the interannual variation showed an upward trend, with an increasing rate of 2.28 mm/a (P<0.05). WYs are high in the south, low in the north, and high in the northwest. Except for the southeast, WYs remained stable or increased in other regions. (2) The relative importance of the main influencing factors of WYs in AEGC successively were precipitation (1.57), evapotranspiration (1.29), temperature (1.12), population density (1.10), net primary productivity (NPP 1.06) and land use intensity (1.02). (3) Large-scale regional nature conditions are the primary force driving change in WYs, while in small-scale regions, human activities and land use are the primary drivers of WYs. Our research emphasizes that the effects of various influencing factors on WYs are significantly spatiotemporal heterogeneity, and WYs in different regions respond differently to the changes of influencing factors.